Capital misallocation in China : financial frictions or policy distortions? - Wu, Guiying Laura (2019)
Policy distortions and financial frictions are two leading candidates in generating capital misallocation. This paper designs an identification strategy to separate their effects on average MRPK dispersion across firm ownership, as the average treatment effect on the treated and the selection bias from a policy intervention. Financial frictions are estimated to cause an aggregate TFP loss of 8.3 percent on the intensive margin, which accounts for 30 percent of the capital misallocation observed in China. Using the counterfactual MRPK from a matching procedure, some popular hypotheses on what drive the policy distortions are tested in the matched samples.